Whose perspective? a guide to gender-sensitive analysis of the media : training manual (Women's Media Watch Jamaica KingstonJM, 1998)
Focuses on aspects such as gender images in the media; gender, media and violence against women; and, criteria for critiquing the media. Presents suggestions for organizing a workshop on gender and the media.
Bibliography: p. 79-80